2020
DOI: 10.3389/fbioe.2020.590549
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Based Scaffold Strategies for Spinal Cord Repair and Regeneration

Abstract: The injury to the spinal cord is among the most complex fields of medical development. Spinal cord injury (SCI) leads to acute loss of motor and sensory function beneath the injury level and is linked to a dismal prognosis. Currently, while a strategy that could heal the injured spinal cord remains unforeseen, the latest advancements in polymer-mediated approaches demonstrate promising treatment forms to remyelinate or regenerate the axons and to integrate new neural cells in the SCI. Moreover, they possess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…3D nanoscaffolds are usually composites composed of some natural polymers (eg, chitosan, collagen, hyaluronic acid (HA), or fibrin) and synthetic nanomaterials (eg, PLGA, PCL, CNTs, or GO). 103 Natural source nanomaterials can guarantee biocompatibility for stem cell differentiation due to their good biodegradability and low antigenicity, 103 , 104 while synthetic nanomaterials can be modified in terms of surface topography, mechanical properties, and electrical properties, which make them favorable for the differentiation of stem cells into neural cells. 105 , 106 Although 3D nanoscaffolds have shown great application prospects in nerve regeneration for degenerative diseases, nanocomposites are often restricted due to their nonbiodegradability, poorly controlled release of drugs, and limited biocompatibility, thus delaying their clinical application.…”
Section: Combined Nanotherapeutic and Stem Cell Therapeutic Strategie...mentioning
confidence: 99%
“…3D nanoscaffolds are usually composites composed of some natural polymers (eg, chitosan, collagen, hyaluronic acid (HA), or fibrin) and synthetic nanomaterials (eg, PLGA, PCL, CNTs, or GO). 103 Natural source nanomaterials can guarantee biocompatibility for stem cell differentiation due to their good biodegradability and low antigenicity, 103 , 104 while synthetic nanomaterials can be modified in terms of surface topography, mechanical properties, and electrical properties, which make them favorable for the differentiation of stem cells into neural cells. 105 , 106 Although 3D nanoscaffolds have shown great application prospects in nerve regeneration for degenerative diseases, nanocomposites are often restricted due to their nonbiodegradability, poorly controlled release of drugs, and limited biocompatibility, thus delaying their clinical application.…”
Section: Combined Nanotherapeutic and Stem Cell Therapeutic Strategie...mentioning
confidence: 99%
“…The limited survival and neuronal differentiation rates of transplanted NSCs are the major hurdles for neural regeneration and functional recovery after SCI 23 . In this study, we first demonstrated that the knockout of NF-1 improved the antiapoptotic and neuronal differentiation abilities of NSCs via the enhancement of the mTORC2 signaling pathway in vitro and in vivo, and the transplantation of NSCs with NF-1 knockout increased tissue repair and neurological recovery in rats subjected to SCI.…”
Section: Discussionmentioning
confidence: 99%
“…100 Various other polymer based approaches for spinal cord regeneration have also been recently reviewed. [101][102][103][104] Biomaterials have also emerged as promising therapeutic strategies for cell delivery to the brain. A recent study showed improved activity of MSCs and vascular endothelial cells (ECs) on 3D spheroids as compared to conventional mixed cell suspensions.…”
Section: Central Nervous Systemmentioning
confidence: 99%